This will only hurt a little ebook - Philipps, Busy (A Bestselling Celebrity Memoir., 2018)
A hilarious, heartfelt, and refreshingly honest memoir and New York Times bestseller by the beloved comedic actress known for her roles on Freaks and Geeks , Dawson's Creek , and Cougar Town who has become "the breakout star of Instagram stories...Imagine I Love Lucy mixed with a modern lifestyle guru" ( The New Yorker ). There's no stopping Busy Philipps. From the time she was two and "aced out in her nudes" to explore the neighborhood (as her mom famously described her toddler jailbreak), Busy has always been headstrong, defiant, and determined not to miss out on all the fun. These qualities led her to leave Scottsdale, Arizona, at the age of nineteen to pursue her passion for acting in Hollywood. But much like her painful and painfully funny teenage years, chasing her dreams wasn't always easy and sometimes hurt more than a little. In a memoir "that often reads like a Real World confessional or an open diary" ( Kirkus Reviews ), Busy opens up about chafing against a sexist system rife with on-set bullying and body shaming, being there when friends face shattering loss, enduring devastating personal and professional betrayals from those she loved best, and struggling with postpartum anxiety and the challenges of motherhood. But Busy also brings to the page her sly sense of humor and the unshakeable sense that disappointment shouldn't stand in her way—even when she's knocked down both figuratively and literally (from a knee injury at her seventh-grade dance to a violent encounter on the set of Freaks and Geeks ). The rough patches in her life are tempered by times of hilarity and joy: leveraging a flawless impression of Cher from Clueless into her first paid acting gig, helping reinvent a genre with cult classic Freaks and Geeks , becoming fast friends with Dawson's Creek castmate Michelle Williams, staging her own surprise wedding, conquering natural childbirth with the help of a Mad Men –themed hallucination, and of course, how her Instagram stories became "the most addictive thing on the internet right now" ( Cosmopolitan ). Busy is the rare entertainer whose impressive arsenal of talents as an actress is equally matched by her storytelling ability, sense of humor, and sharp observations about life, love, and motherhood—"if you think you know Busy from her Instagram stories, you don't know the half of it" (Jenni Konner). Her conversational writing reminds us what we love about her on screens large and small. From "candid tales of celebrity life, mom life, and general Busy-ness" ( W Magazine ), This Will Only Hurt a Little "is everything we've been dying to hear about" ( Bustle ).